New Records of Helminth Parasites in Amphibians from the South American Chaco - González , M. A.; Villegas Ojeda , M. A.; Caraballo , J. N.; Ailán Choke , L. G.; Hamann, M. I.; Duré , M. I.; Gómez , V. I.; González , C. E. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2024)
This study aims to identify the helminth fauna of twelve anurans species from Argentina's Dry and Humid Chaco ecoregions. We collected one hundred and fifty-two specimens belonging to the species Dendropsophus nanus (n = 17), Scinax nasicus (n = 15), Pithecopus azureus (n = 7), Pseudis platensis (n = 10), Trachycephalus typhonius (n = 7) (Hylidae), Leptodactylus bufonius (n = 3), L. latinasus (n = 16), L. luctator (n = 14), L. macrosternum (n = 12), Physalaemus santafecinus (n = 14), P. albonotatus (n = 11) (Leptodactylidae), and Elachistocleis haroi (n = 26) (Microhylidae) from 3 areas located in the provinces of Chaco and Formosa (Dry Chaco) and in Corrientes province (Humid Chaco). A total of 17 helminth taxa were found; acanthocephalans in the larval stage (Centrorhynchidae: Centrorhynchus sp.) and nematodes in the larval stage (Anisakidae: Contracaecum; Ascarididae: Porrocaecum; Physalopteridae: Physaloptera; aff. Cystidicolidae) and adult stage (Rhabdiasidae: Rhabdias sp., R. elegans; Strongyloididae: Strongyloides pereirai; Molineidae: Oswaldocruzia proencai, O. subauricularis; Pharyngodonidae: Parapharyngodon senisfaciecaudus cubensis; Cosmocercidae: Aplectana hylambatis, Cosmocerca parva, C. podicipinus, Cosmocercella phyllomedusae, Schrankiana formosula; Kathlaniidae: Falcaustra mascula). This study presents new host and geographic records and expands knowledge of helminth diversity in a critically threatened group of vertebrates.